Nitrogen transformations in two rice soils of Rio Grande do Sul under submerged conditions - Morais, José Francisco Valente; Freire, Claúdio José da Silva; Silva, Enedino Corrêa da (Pesquisa Agropecuaria Brasileira, 2014)
A laboratory experiment was conducted with the objectives of studying nitrogen transformation in two rice soils of Rio Grande do Sul. Samples of the soils were treated with 100, 120, and 100 kg/ha of N, P, and K, respectively, applied as (NH4)2HPO4, K2HPO4 and KCl. The treated soils were then adjusted to moisture contents approximating their field moisture capacities and incubated at room temperature for periods of 0, 7, 14, 28, 42, or 56 days. At the end of each incubation period the soils were flooded soil percolate collected every 7 days, and percolates analyzed for nitrate (NO3) and ammonium (NH4). Exchangeable ammonium was measured in each soil after flooding was terminated. The analytical results were used to calculate the extent and rate of nitrogen transformations. Oxidation of nitrogen of ammonium was a direct function of the amount of time during which the treated soils were incubated at field moisture capacity prior to flooding. Soil type also significantly influenced the rate of ammonium oxidation.
Keywords: Nitrification; nitrification rates; nutrient leaching